PENGARUH KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, MASA PERIKATAN AUDIT, DAN REPUTASI AUDITOR TERHADAP OPINI AUDIT GOING CONCERN - Fitria, Nada (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims to examine the effect of company financial condition, company size, audit tenure, and the auditor reputation on going concern audit opinion. The purposive sampling used in this study acquires the samples of 27 manufacturing companies listed on Indonesia Stock Exchange between 2015 and 2019 with 135 observable companies, analyzed by logistic regression. The result of the study indicates that company financial condition and reputation of auditors have negative and positive effect on going concern audit opinion respectively. Whilst, company size and audit tenure do not have significant effect on going concern audit opinion. The study findings reveal that the worse the company's financial condition and the better the auditor's reputation, the more likely it is to get an opinion going concern.Keywords: going concern audit opinion, financial condition, company size, audit tenure, reputation of audito